Does hazardous waste matter? evidence from the housing market and the Superfund program - Greenstone, Michael 1968-; Gallagher, Justin (National Bureau of Economic Research, 2005)
"Approximately
Keywords: United States. -- Superfund Amendments and Reauthorization Act of 1986; Hazardous waste site remediation -- Economic aspects -- United States; Housing -- Prices -- United States; USA